"Impossible Families": Mixed‐Citizenship Status Couples and the Law. (9th March 2015) - López, Jane Lilly
Abstract : This article explores the complex and contradictory relationship between citizenship in the law and the immigrant reality of mixed‐citizenship family life through in‐depth interviews with individuals in mixed‐citizenship marriages. An examination of mixed‐citizenship marriage exposes the inadequacies of approaching citizenship as an individual‐centered concept. The data indicate that, though both immigration and citizenship laws focus on the individual, the repercussions of those laws have family‐level effects. Because of their spouses' immigrant status, many citizens are obliged by the law to live the immigrant experience in their own country or to become immigrants themselves.